Influence of cycle time on sewage treatment using sequencing batch reactor - Thomas, M.V.; Agamuthu, Pariatamby (Faculty of Science, University of Malaya, 2003)
A Sequencing Batch Reactor (SBR) was tested for performance under two different cycle times - 8 hours per cycle and 6 hours per cycle. The effluent quality after treatment was compared against specified effluent quality limits to determine the plant’s performance in terms of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Suspended Solids (SS), ammonia-nitrogen, nitrate-nitrogen, and phosphorus. The reduction of BOD, COD, SS and nitrate-nitrogen content in the SBR was not significantly affected by the cycle time — the levels under both time cycles complied with the effluent limits imposed. In fact, the SBR plant provides excellent treatment performance for conventional parameters of BOD, COD and SS, as well as nitrate-nitrogen at both 6-hour and 8-hour cycles. However, the study showed that removal efficiency of ammonia-nitrogen and phosphorus was better using the 8-hour cycle, compared to the 6-hour cycle. Nevertheless, it is has been established that the SBR would require a stabilisation period of at least three months for optimum phosphorus removal. Data obtained from this study is expected to be useful in the selection of the optimal cycling times in SBR for tropical conditions.